Biodiversity of Endophytic Fungi Associated with Uncaria gambier Roxb. (Rubiaceae) from West Sumatra - MUHAMMAD ILYAS; ATIT KANTI; YULIASRI JAMAL; HERTINA HERTINA; ANDRIA AGUSTA (Society for Indonesian Biodiversity, 2009)
Endophytic fungi are specific microbes that live at a specific ecosystem in nature. Various endophytic fungi have been known posses an ability to produce a broad range of biologically active substances. Totally 53 endophytic filamentous fungi were isolated from leaves, stems, fruits and roots of the two plant varieties of Uncaria gambier Roxb. (Rubiaceae), i.e. gambir udang and gambir nasi. Morphological observation of 53 isolated endophytic filamentous fungi was further divide into two classes, Coelomycetes and Hypomycetes. Fifteen fungi isolates are unidentified due to lack of specific morphological characters. Morphologically identified fungi at genera level are: Aspergillus, Cladosporium, Diaporthe, Fusarium, Penicillium, Pestalotiopsis, Phoma and Phomopsis. Chemotaxonomic analysis base on their TLC chromatogram patterns of the ethyl acetate extract are in agreement to morphological grouping.Key words: endophytic fungi, Uncaria gambier Roxb., morphological character, chemotaxonomy.